Pengaruh Ewom Quality, Ewom Quantity, dan Customer Relationship Terhadap Kepuasan Pembelian di Toko Rizal Aluminium dan Kaca - Rizal Dwi Prasetya; Erry Setiawan; Dwi Sembe Sigita (Formosa Journal of Social Sciences (FJSS), 2022)
The purpose of this study was to determine: (1) The effect of Ewom Quality partially on customer satisfaction at the Rizal Aluminum and Kaca Store (2) The effect of Ewom Quantity partially on customer satisfaction at the Rizal Aluminum and Glass store (3) The effect of partial Customer Relationship on customer satisfaction at Rizal Aluminum and Glass Stores (4) The influence of Ewom Quality, Ewom Quantity, and Customer Relationship simultaneously on customer satisfaction at Rizal Aluminum and Glass stores. The population in this study were all customers of Rizal Aluminum and Glass Stores. The number of samples based on the Non Probability sampling technique and also using the Slovin formula was 85 respondents with the data distribution technique using the Accidental Sampling technique. The data were analyzed using the Multiple Linear Regression method, to partially test the hypothesis using the t test, while simultaneously using the F test to test the hypothesis. The results of this study are (1) Ewom Quality has a partial (individual) effect on customer satisfaction (2) Ewom Quantity no partial (individual) effect on customer satisfaction (3) Customer Relationship has no partial (individual) effect on customer satisfaction (4) Ewom Quality, Ewom Quantity, and Customer Relationship influence simultaneously (together) on customer decisions at Rizal's shop Aluminum and Glass.